Improving management of BUMDES for village development - Malik, Andi Abdul; Gani, Hamsu Abdul; Rifdan, Rifdan (Linguistics and Culture Review, 2021)
The purpose of this study is to examine and explain the management strategy of BUM Desa in realizing an Independent Village. The type of research used is descriptive qualitative, using a case study approach (case study). The focus of the research is the management of BUM Desa. Data obtained through primary and secondary data sources. Data collection techniques through interviews, observations, questionnaires and literature. The research instrument is the researcher himself. Data analysis is carried out in stages; data collection, data simplification, data presentation and conclusion drawing. The results of the SWOT analysis on the WT strategy (weaknesses and challenges) formulating a BUMDES management strategy with the Cadreization-Based Management Intervention Model show that BUMDES management is related to BUMDES institutional managerial so that the Village Government can accelerate the development and performance improvement of BUMDES management in the management of BUMDES to realize an Independent Village.